Adjudicatory Oversight and Judicial Decision Making in Executive Branch Agencies. (July 2013) - Boyd, Christina L.; Driscoll, Amanda
Adjudications are an important, though understudied, means through which administrative agencies create policies that have a lasting impact. We argue that executive branch agency heads utilize their oversight of agency adjudications to advance agency goals. Relying on an original data set of adjudications appealed to the U.S. Department of Agriculture's agency head's adjudication delegee, our empirical results indicate a substantial positive effect on the probability that the agency head will reverse an administrative law judge (ALJ) when he receives the appeal of an antiagency ALJ decision. However, the agency's adjudication oversight is conditional on political constraints, including partisanship differences between an agency and the litigated law and whether the case is being heard during a time of presidential transition. These results have clear implications for the use and effectiveness of agency adjudications as a political tool.